Flexibility and constraints in the molt schedule of long‐distance migratory shorebirds: causes and consequences. Issue 7 (23rd May 2013) - Barshep, Yahkat; Minton, Clive D. T.; Underhill, Les G.; Erni, Birgit; Tomkovich, Pavel
Abstract Molt is a major component of the annual cycle of birds, the timing and extent of which can affect body condition, survival, and future reproductive success through carry‐over effects. The way in which molt is fitted into the annual cycle seems to be a somewhat neglected area which is both of interest and of importance. Study of the causes of annual variation in the timing of molt and its potential consequence in long‐distance migratory birds was examined using the Curlew Sandpiper, Calidris ferruginea, as a model species. Using the maximum likelihood molt models of Underhill and Zucchini (1988, Ibis 130:358–372), the relationship between annual variability in the start dates of molt at the population level with conditions on the breeding area was explored. Adult males typically started early in years when temperature in June on the Arctic breeding grounds were high compared to cold years while adult females molted later in years of high breeding success and/or warm July temperature and vice versa. When molt started later, the duration was often shorter, indicating that late completion of molt might have fitness consequences, probably jeopardizing survival. Evidence of this was seen in the low body condition of birds in years when molt was completed late. The results indicate that these migratory shorebirds follow a fine‐tuned annual life cycle, and disturbances at a certain stage can alter next biological events through carry‐over effects.